2021
DOI: 10.3390/ani11051237
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the PRLR Gene and Their Association with Milk Production Traits in Egyptian Buffaloes

Abstract: Prolactin (PRL) and its receptor (PRLR) were considered as potential genetic markers for milk production and quality traits in cattle. However, little information is available regarding PRLR genetic diversity and association studies with milk traits in Egyptian water buffaloes. Therefore, the present study was conducted to search for mutations in PRLR and determine their associations with milk performance in these animals. Exon3 (E3) and E10 of PRLR were screened for polymorphisms using single strand conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…According to Chu et al, the PRLR gene closely related to prolactin signaling pathway is a candidate gene for prolificacy of small tail trait in han sheep 33 . In Egyptian Buffaloes, the PRLR has shown promise as a genetic marker for evaluating milk production and quality traits 34 . Additionally, another gene associated with the prolactin signaling pathway, MAPK13 (mitogen-activated protein (MAP) kinase family), exhibited downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chu et al, the PRLR gene closely related to prolactin signaling pathway is a candidate gene for prolificacy of small tail trait in han sheep 33 . In Egyptian Buffaloes, the PRLR has shown promise as a genetic marker for evaluating milk production and quality traits 34 . Additionally, another gene associated with the prolactin signaling pathway, MAPK13 (mitogen-activated protein (MAP) kinase family), exhibited downregulation.…”
Section: Discussionmentioning
confidence: 99%
“…From an animal breeding perspective, our prior study identified the most significant locus associated with teat number in the ABCD4 region [ 8 ], a finding supported by recent research [ 25 ]. Meanwhile, polymorphisms of the PRLR gene have been associated with reproductive traits and milk production traits in pigs, goats, sheep and dairy cattle [ 37 40 ]. Specifically, animals with different PRLR genotypes show significant differences in the number of functional teats, age at first estrus, litter size, and litter average [ 22 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Chu et al, the prolactin receptor (PRLR) is a candidate gene for proli cacy of small tail han sheep 36 . In Egyptian Buffaloes, the Prolactin receptor (PRLR) has shown promise as a genetic marker for evaluating milk production and quality traits 37 . The current experiment revealed a signi cant upregulation of the PRLR gene by a log2FC of 3.05.…”
Section: Discussionmentioning
confidence: 99%